P1778 Preeclampsia is associated with reduced myocardial work efficiency during pregnancy. (17th January 2020) - Chow, Y Y; Chapman, M; Mahadevan, D; Dekker, G; Arstall, M
Abstract: : AIM Preeclampsia (PrE) is a systemic disorder unique to human pregnancy, which is characterised by hypertension and multiorgan involvement. It is associated with cardiac dysfunction with a reduction in global longitudinal strain (GLS) and long-term cardiovascular disease. The aim of this study is to evaluate the effects of the loading conditions on the GLS results utilising myocardial work (MW) a non-invasive assessment of left ventricular (LV) pressure strain loops. Methods: We evaluated 41 pregnant women, aged between 18-40, at 28.4-40 (Mean 35) weeks of gestation and within one week of the diagnosis of PrE. 49 normotensive pregnant women (control) were matched for age and gestation. These patients were reassessed after six months postpartum. All patients underwent echocardiography for left ventricular indices and assessment with speckle tracking for global longitudinal strain (GLS%) and myocardial work indices - performed at both time points. Result: PrE had a mean LV mass index (LVMi) of 14.53g.m2 higher than control (P value = 0.000) during pregnancy which normalised at six-months postpartum. There was a reduction in GLS between PrE and controls during pregnancy (p = 0.002) and this remained significant postpartum (p = 0.001). (Fig1) However, there was no change over time within each group. During pregnancy, peak global myocardial work efficiency (GWE%) in PrE was significantly lower than controls (p = 0.001) and no different six months postpartum (p = 0.169) (Fig2). In contrast, during pregnancy, myocardial work index (GWI mmHg) was significantly higher in PrE (p < 000) compared to control, but not in postpartum (p = 0.165) There was a significant change over time of GWI in both groups (p < 0.05) (Fig3). Conclusion: During pregnancy and post-partum PrE patients show a reduction in GLS when compared to matched normotensive pregnant women. This finding is consistent with previous studies which suggests subclinical LV dysfunction in PrE. However, the GWI was significantly increased but reduced in efficiency (GWE). The GWI increase is likely a result of an increase in LV mass index. The hypertrophied LV allows the increase in work at the cost of a reduction in efficiency but normalises when the hypertrophy improves post-partum. Our study is the first to use myocardial work in PrE patients, which we believe provides a better assessment of cardiac adaptation post-partum and does not suggest long term subclinical LV dysfunction.